Dr. Amanda E. Schwint: enjoy every step of the way and admit “there are always more questions than answers” - Lin, Teresa (Therapeutic Radiology and Oncology, 2018)
The 18th International Congress on Neutron Capture Therapy was held successfully for the first time in Taipei, Taiwan from October 28 through November 2, 2018. The congress was spread over six days and featured training courses, parallel sessions, plenary talks, invited lectures, and poster viewing and presentations.